(untitled) (Global Journal of Management and Business Research, 2020)
Rural growth center can play a vital role in developing the economic condition of the rural people by acting as a prime stage for buying and selling agricultural products. This study analyzes the existing scenario and also reveal the problems of the growth center. The study market meets a great demand of the people of the surrounding area. This helps to create a various opportunity for the residence and also makes a great change to the lifestyle of the residence.